2016
DOI: 10.1088/1361-651x/25/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiolocal-energy and local-stress analysis of tensile behaviours of tilt grain boundaries in Al and Cu

Abstract: Tensile deformation and failure of Σ9 tilt grain boundaries (GBs) in Al and Cu have been examined by first-principles tensile tests (FPTTs). Local-energy and local-stress schemes were applied to clarify the variations of local energies and local hydrostatic stresses for all atoms during the deformation process. The GBs in Al and Cu exhibited quite different tensile behaviours in the FPTTs, despite their similar initial configurations. For the Al GB, there are two stages of deformation before failure. In the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
0
17
1
1
Order By: Relevance
“…N segregation at I4 site Figure 3d is the atomic energy of each Al atom. When an interstitial atom is added, the atomic energy of the two Al atoms on each layer is different due to its long-ranged sp orbitals [27,44]. By comparing the Al atomic energy in each layer in the pure twin, it can be found that when the C is added, the Al13 atomic energy is more greatly reduced than Al14 on TB.…”
Section: Twin Model With C N H and Omentioning
confidence: 99%
“…N segregation at I4 site Figure 3d is the atomic energy of each Al atom. When an interstitial atom is added, the atomic energy of the two Al atoms on each layer is different due to its long-ranged sp orbitals [27,44]. By comparing the Al atomic energy in each layer in the pure twin, it can be found that when the C is added, the Al13 atomic energy is more greatly reduced than Al14 on TB.…”
Section: Twin Model With C N H and Omentioning
confidence: 99%
“…These values are even higher than those reported previously for fcc FeCoNi and CrFeCoNi [22], indicating larger local stresses in refractory bcc HEAs than in 3d-transition-element fcc HEAs. The computed atomic stresses are also substantially higher than those at dislocation cores in bcc Fe [68,69], fcc Al [70], and B2 TiNi [71] as well as higher than the atomic stresses at grain boundaries of bcc Fe [30][31][32] and fcc Al and Cu [25,[33][34][35].…”
Section: A Distributions Of Atomic Volumes Charges and Stressesmentioning
confidence: 80%
“…To compute atomic stresses we utilized the concept of stress densities. Electronic-structure-based stress densities have been widely used to analyze local properties, e.g., at grain boundaries [25,[30][31][32][33][34][35][36], at surfaces [37][38][39], in superlattices [40], to analyze chemical bonding in molecules [41][42][43], in metal clusters [44][45][46], in metal complexes [47], in lithiumionic conductors [48], and in Si-Fe [49], as well as to analyze electronic shell structures of atoms [50]. In the present study, the method by Filippetti and Fiorentini [51], later modified to fit the plane-wave basis projector augmented-wave (PAW) method [37], was employed to compute the stress density.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This local-energy analysis scheme, incorporated in the computational code QMAS [14], has already been applied to defect systems such as fcc-Al (111) surfaces [7], fcc-Al and fcc-Cu [110] GBs [15,16,17], and bcc-Fe [110] GBs [18,19]. We use the generalized gradient approximation [20] for the exchangecorrelation functional and a cut-off energy of 544 eV for the valence wave function.…”
Section: Calculation Of Dft-based Atomic Energymentioning
confidence: 99%